Pengetahuan Dan Sikap Remaja Putri Terhadap Perilaku Sadari Sebagai Deteksi Dini Kanker Payudara - Jaya, Herawati; Rosnani, Rosnani; Ningsih, Ratna (JKM : Jurnal Keperawatan Merdeka, 2025)
Background: Adolescence is a transitional period characterized by rapid physical, psychological, and intellectual growth and development, making adolescents vulnerable to reproductive health problems. One non-communicable disease in adolescents that increases annually is breast cancer. This study aims to determine the knowledge and attitudes of adolescent girls regarding breast self-examination (SADARI) as an early detection of breast cancer. By conducting a SADARI examination, immediate action can be taken if abnormalities are found. Method: This study used an observational, analytic, cross-sectional design. The sample was selected using a purposive sampling technique. The total sample size was 33 respondents. Data were analyzed using univariate and bivariate analysis. Results: After data processing, the results showed a significant relationship between knowledge (p-value = 0.002 (p<0.05) and attitude (p-value = 0.000 (p<0.05) and SADARI behavior. Conclusion: There is a relationship between adolescent girls' knowledge and attitudes and SADARI behavior as an early detection of breast cancer.